Estetrol: a new estrogen component in combined oral contraceptives: A review - Aida U. Hamadyanova; Afzal H. Tuhtaboev; Venera A. Shafieva; Elena A. Kolodyazhnaya; Julia R. Mansurova; Aliya A. Muratova; Arina A. Andreeva; Julia A. Muzafarova (IP Berlin A.V., 2023)
Estetrol (E4) is a steroid hormone found in the urine of pregnant women in 1965. E4 is produced only during pregnancy and enters the maternal bloodstream through the placenta. Its concentration in maternal human plasma increases during pregnancy, reaching a maximum by the end of pregnancy (1 ng/mL). The pharmacological properties of E4 make it a promising agent for hormonal therapy and contraception. To date, phase II and III studies have shown promising results with the combination of 15 mg of E4 and 3 mg of drospirenone: this combined oral contraceptive has shown a good effect with a neutral metabolic effect. However, evidence is scarce about the effect of the new combination on the breast and bone tissue. Further studies are needed to consolidate the available data and to investigate possible side effects of prolonged use of E4-containing combined oral contraceptives compared to known ethinylestradiol and estradiol-containing combinations.